The use of Iron Sand as Filtration Media for Slaughterhouse Wastewater Treatment - Hamdan, Abd Mujahid; Ikbar, Athalla Muafa; Bhernama, Bhayu Gita (JRST (Jurnal Riset Sains dan Teknologi), 2024)
An increase in slaughtering animals will have an impact on increasing the liquid waste produced. The resulting RPH liquid waste can damage the environment if it is not treated, so it is necessary to conduct research to reduce pollutant levels so that it is suitable for disposal into the environment. The technique used in processing RPH wastewater is iron sand filtration method. Iron sand filtration is a filtering process using renewable media, namely iron sand. Iron sand is known to contain the mineral magnetite (Fe3O4) which has the ability to absorb colloidal solids, so it has the potential to be used to remove pollutant content of RPH liquid waste. This research objective to determine the effect of variations in the thickness of the filtration media (cm) and grain size (mesh) on pollutant parameters. The thickness variations used were 20, 25, and 30 cm, with grain sizes of iron sand 40, 60 and 100 mesh. The experimental results showed that the iron sand filtration method was able to reduce Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) levels, increase the Dissolve Oxygen Meter (DO) value, and change the pH value. The highest reduction in COD was in the thickness variation of 30 cm with 100 mesh. the percentage of decrease in the value of Chemical Oxygen Demand (COD) was 95.05%, the highest decrease in Total Suspended Solid (TSS) value was in the media thickness variation of 30 cm with 100 mesh, the percentage of TSS value reduction was 97.11%, the pH value increased in the thickness variation media 30 cm with a mesh number of 100 from 5.8 to 7.4, and the value of Dissolve Oxygen Meter (DO) increased with variations in thickness of 30 cm with 100 mesh, increased from 1.2 to 15.2. Based on the parameter test results, it was concluded that iron sand filtration is effective in reducing pollutant levels below the quality standard, so that it is expected to be applied directly on a larger scale.